2000
DOI: 10.1046/j.1460-9568.2000.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the medial septum in stress‐induced relapse to heroin seeking in rats

Abstract: Intermittent footshock stress has been shown to reinstate extinguished drug-taking behaviour in rats, but the brain areas involved in this effect are to a large degree unknown. Here we studied the role of the septum in stress-induced reinstatement of heroin seeking. Rats were trained to self-administer heroin for 9-10 days (three 3-h sessions per day, 0.1 mg/kg per infusion). Following training, extinction sessions were given for 8-13 days by substituting saline for heroin, and then tests for reinstatement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…Role of impulsivity in effects of muscimol on alcohol seeking Earlier studies on stress-induced reinstatement of drug and alcohol seeking suggested that stress might induce relapse to drug use by impairing the operation of an inhibitory behavioural control system (Highfield et al 2000;. The fact that intra-MRN injections of muscimol induce a variety of behaviours ranging from water Stratford and Wirtshafter 2000), food Wirtshafter 1988, 1989), and alcohol consumption (Tomkins et al 1994) and locomotor activity suggest that the projections originating in the MRN may be a part of such an inhibitory control system.…”
Section: Discussionmentioning
confidence: 99%
“…Role of impulsivity in effects of muscimol on alcohol seeking Earlier studies on stress-induced reinstatement of drug and alcohol seeking suggested that stress might induce relapse to drug use by impairing the operation of an inhibitory behavioural control system (Highfield et al 2000;. The fact that intra-MRN injections of muscimol induce a variety of behaviours ranging from water Stratford and Wirtshafter 2000), food Wirtshafter 1988, 1989), and alcohol consumption (Tomkins et al 1994) and locomotor activity suggest that the projections originating in the MRN may be a part of such an inhibitory control system.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study demonstrates that only morphineconditioned withdrawal reinstates morphine CPP, which may be a stress-driven effect (Lu et al 2005). Thirdly, it has also been suggested that stress may provoke relapse by interfering with neuronal inhibitory processes, which inhibits responding when reinforcers are not available (Highfield et al 2000). In support of this idea, it has been observed that footshock stress increases resistance to extinction, and footshock's reinstating effects depend on the manipulation of the medial septum, a brain area involved in response inhibition (Highfield et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The coordinates (Paxinos and Watson, 2005) for the NAc core (61 angle aimed medially) were AP + 1.6, ML72.5, and DVÀ6.0; coordinates for the NAc shell (61 angle aimed medially) were AP + 1.6, ML71.7, and DVÀ6.5; coordinates for the caudate-putamen (61 angle aimed medially) were AP + 1.6, ML72.5, and DVÀ4.5. Following cannulae implantation, silastic catheters were inserted into the jugular vein and were passed subcutaneously to the top of the skull, as described previously (Highfield et al, 2000;Shaham et al, 2000b). The catheters were then attached to a modified 22-gauge cannula (Plastics One, Roanoke, VA) and mounted to the rat's skull with dental cement.…”
Section: Intracranial and Intravenous Surgerymentioning
confidence: 99%